Evaluation of life quality in patients with postinfarction cardiosclehrosis on the background of metabolitic therapy - Semenchuk, Svitlana; Stotska, Tamara (ScienceRise: Medical Science, 2017)
Aim of research – to estimate the dynamics of life quality indices in patients with postinfarction cardiosclerosis on the background of the metabolic therapy using the questionnaire MacNew Heart Disease Health-related Quality of Life. Materials and methods: in the research took part 99 patients (71 % of men and 29 % of women) with postinfarction cardiosclerosis, stable angina of effort of ІІ-ІІІ functional class. Patients of the group of comparison (n=49) continued to take the basis therapy of the ischemic heart disease, whereas patients of the main group (n=50) additionally took glutargin. All groups were representative by age and sex. The patients’ life quality estimation was realized by the questionnaire MacNew. Results: The determination of the life quality was carried out using the questionnaire MacNew Heart Disease Health-related Quality of Life, most effective for patients with the ischemic heart disease. At the comparative analysis of initial life quality indices by the questionnaire MacNew in both groups, all patients with postinfarction cardiosclerosis demonstrated the decrease of all indices of scales and didn’t differ statistically. It was established, that on the background of glutargin treatment took place the statistically reliable increment of the physical activity (from 4,3±1,0 to 5,2±0,9 points, p<0,05) and reliable increase of the routine activity, limited by the pain influence (from 4,6±0,8 to 5,9±0,9 points, p<0,05). Conclusions: All patients with postinfarction cardiosclerosis demonstrated the essential decrease of life quality indices in physical, emotional and social spheres. Glutargin inclusion into the standard therapy of patients with the ischemic heart disease allows to improve the life quality of patients with postinfarction cardiosclerosis essentially